Video feedback in sport: Review of behavioral-analytic literature (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The purpose of this article was to conduct a behavior-analytic review on interventions with video feedback in sports. A search was performed using capes, PsycINFO, SPORTdiscus, Web of Science, Pepsic, Indexpsi, Scielo, Pubmed and Google Scholar databases. The keywords video feedback, feedback in video, feedback, intervention with video and task analysis were combined with the keywords volleyball, sport, futsal, handball, basketball, and soccer. The same keywords were combined with the keyword behavior analysis in English and Portuguese. Results showed a prevalence of studies with amateur participants of individual sport modalities which investigated the effects of using video feedback alone or video feedback with an expert model. Only technical skills were investigated, which could indicate a gap in the literature on the effectiveness of tactical variables on individual and collective modalities with high performance athletes.
Keywords: sport; video feedback; behavior analysis